Caracterización de la cadena de abastecimiento para accesorios tecnológicos desde China a Colombia: caso importación de auriculares Tecni.cel. (2023)
The inquiry was carried out for the purpose of implement improvements in Tecni.cel micro-Enterprise, with the use of the supply chain in the imports of technological accessories in Colombia that help satisfy the demand for goods of the population. The import of headphones from China to Colombia is a common business activity, it is a major exporter of electronics, including headphones.